1999
DOI: 10.1046/j.1365-2559.1999.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c‐erbB‐2 oncoprotein in human thyroid tumours

Abstract: Our results indicate that overexpression of c-erbB-2 oncoprotein is easily identifiable by immunohistochemistry in paraffin sections of certain thyroid tumours after applying an antigen retrieval method. This study suggests that c-erbB-2 oncoprotein may play some role in disease progression in papillary and medullary thyroid carcinomas, but the significance of the different immunohistochemical patterns merits further investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…In some of our cases, however, we observed variable cytoplasmic expression of HER-2. The relevance of this finding, as in other tumors, is currently unknown [12,13,15,[33][34][35]. Our findings indicate that potential targeted therapy of ATC with trastuzumab (Herceptin; Genetech Inc., South San Francisco, CA) may be considered individually.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In some of our cases, however, we observed variable cytoplasmic expression of HER-2. The relevance of this finding, as in other tumors, is currently unknown [12,13,15,[33][34][35]. Our findings indicate that potential targeted therapy of ATC with trastuzumab (Herceptin; Genetech Inc., South San Francisco, CA) may be considered individually.…”
Section: Discussionmentioning
confidence: 57%
“…Studies of HER-2 in thyroid tumors have reported an association between overexpression and aggressive behavior in differentiated thyroid carcinomas [12][13][14]. Interestingly, low or loss of HER-2 expression has been reported in undifferentiated thyroid tumors, suggesting that its downregulation plays a role in the biologic progression of some of these tumors [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Utrilla et al (20) investigated 67 thyroid tumors (10 follicular adenomas, 11 follicular carcinomas, 3 anaplastic carcinomas, 25 papillary carcinomas, 18 medullary carcinomas and 16 metastases) for HER-2 expression by IHC using an antigen aretrieval method for paraffin-embedded material and a specific polyclonal antibody against the intracytoplasmic part of the HER-2 oncoprotein. No expression of this oncoprotein was detected in follicular adenomas, follicular carcinomas and anaplastic carcinomas; however, 52% of the papillary carcinomas (some membranous staining, but mostly diffuse cytoplasmic staining patterns) and all the medullary carcinomas (granular cytoplasmic staining pattern) were immunopositive.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no striking difference between the prognosis of patients with follicular carcinoma and papillary carcinoma, regulation of some other type than caveolin-1 must operate for signal transduction in follicular carcinomas. A previous study observed that c-erbB-2 oncoprotein was expressed in more than 50% of papillary carcinomas but not in follicular carcinomas or undifferentiated carcinomas (Utrilla et al, 1999). The difference in the status of these proteins in papillary and follicular carcinomas reflects the difference of entities between these two types of carcinoma.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 90%